The barriers to education among the Palestinian refugee children in Malaysia - Eid, Iyad Muhammad; Rokis, Rohaiza (2019)
This paper addresses the barriers that prevent Palestinian refugee children from obtaining education during their transition in the host country, Malaysia. It creates awareness among the Palestinian refugee community about this critical issue which threatens the future of their children who might spend many years without receiving adequate learning opportunities. The present study is based on a qualitative approach which is commonly used to explore recent phenomenon and provide an in-depth understanding of human behaviours and beliefs based on their points of view. It collected data employing semi-structured interviews with 30 Palestinian refugee families moving from Iraq, Syria and the Gaza Strip, and currently residing in Malaysia, waiting to be resettled in a third country through the United Nations High Commissioner for Refugees (UNHCR) office in Kuala Lumpur. Using thematic analysis technique, the research shows that there are economic, institutional and parental challenges preventing the Palestinian refugee children from receiving education in Malaysia. Also, it reveals how such challenges lead to negative psychological impacts among the parents and their children. Moreover, it is found that the parents did not play an adequate role in utilising potential alternative pathways to education. Finally, it offers a realistic solution to return these children to a viable education.